Development of Ethnomathematics-Based Student Worksheets to Improve the Understanding of Concepts for Junior High School Grade IX Students - Ayu Pitaloka Saragi; Rusi Ulfa Hasanah (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
Mathematics learning requires innovative and contextual teaching materials so that students can more easily understand concepts. However, the availability of teaching materials is still limited in schools. Often teachers only use package books as the only teaching materials used. This research aims to develop ethnomathematics-based Student Worksheets by integrating the Batak Gorga motif in the translation and reflection materials of grade IX of junior high school. The research model used is Research and Development (R&D) by adapting Borg and Gall's steps to the final product revision stage. The research instruments include expert validation, teacher and student response questionnaires, and concept understanding tests conducted through pre-tests and post-tests. The results of the study show that the average assessment from material and media experts is in the category of very valid. The responses of teachers and students gave an average assessment with a very practical category. In addition, the average results of the students' concept understanding test showed an increase from pre-test to post-test, so that the effectiveness of Student Worksheets was in the medium category. The integration of Gorga Batak motifs in the Student Worksheet is able to help students understand the concepts of translation and reflection more easily. This Student Worksheet can also be used by teachers as teaching materials based on local culture to increase the effectiveness of mathematics learning.